Fiscal Incidence Analysis for Kenya : Using the Kenya Integrated Household Budget Survey 2015-16 - World Bank (World Bank, Washington, DC, 2018)
Kenya has made satisfactory progress in reducing poverty and inequality in recent years. Economic growth in Kenya between 2005-06 and 2015-16 averaged around 5.3 percent, exceeding the average growth of 4.9 percent observed for Sub-Saharan Africa. This robust economic growth resulted in a reduction in poverty, whether measured by the national or international poverty line. The proportion of the population living beneath the national poverty line fell from 46.8 percent in 2005-06 to 36.1 percent in 2015-16, showing a modest improvement in the living standards of the Kenyan population. Similarly, poverty under the international poverty line of US$ 1.90 a day declined from 43.6 percent in 2005-06 to 35.6 percent in 2015-16. At this level, poverty in Kenya is below the average in sub-Saharan Africa and is amongst the lowest in the East African Community (World Bank, 2018b). However, the proportion of the population living in poverty remains comparatively high in Kenya and the rate at which growth translated into poverty reduction was lower than elsewhere. At twice the average, Kenya’s poverty rate is still high for a lower-middle income country, a group that Kenya joined only in 2015. In addition, the Kenya’s growth elasticity of poverty reduction, the percentage reduction in the poverty rate associated with a one-percent increase in mean per capita income is only 0.57, lower than in Tanzania, Ghana, or Uganda (World Bank, 2018b). This leads to the obvious question of what can be done to make economic growth more pro-poor in Kenya. This study assesses the distributional consequences of Kenya’s system of taxes and transfers, covering 60 percent of revenue and between 25 and 30 percent of government spending. The analysis of fiscal incidence and distributional consequences of Kenya’s tax and transfer system is an important input for designing pro-poor policies and potentially for influencing the rate at which economic growth translates into poverty reduction. In this study, direct taxes and transfers, indirect taxes (VAT and excise duties), as well as public health and education spending are assessed in terms of their distributional impacts. Overall, these taxes and transfers account for about 60 percent of revenue and between 25 and 30 percent of government spending.